Nicotine delivery and users' reactions to Juul compared with cigarettes and other e‐cigarette products. (29th January 2020) - Hajek, Peter; Pittaccio, Kate; Pesola, Francesca; Myers Smith, Katie; Phillips‐Waller, Anna; Przulj, Dunja
Abstract: Aims: To assess the pharmacokinetic (PK) profile of, and users' reactions to, Juul (59 mg nicotine/ml) as an indication of its therapeutic and dependence potential. Design: Cross‐over, within‐subjects study in which participants attended after overnight abstinence on separate sessions and smoked a cigarette or used Juul or eight other types of e‐cigarettes (EC) ad libitum for 5 minutes. The Juul product used was the version available in the United States that has more nicotine in the e‐liquid than the one available in the European Union. Setting: Laboratory setting in the United Kingdom. Participants: Twenty dual users (smokers who also vape) provided data on Juul and cigarettes, with eight also providing data on other EC products. Measurements: At each session, number of puffs taken was counted during the 5‐minute product use period and blood samples were taken at baseline and at 2, 4, 6, 8, 10 and 30 minutes after starting smoking/vaping and analysed for nicotine. Participants also monitored their urges to smoke and rated the products on a range of characteristics. Findings: Juul's PK profile was close to the PK profile of cigarettes [maximum concentration (Cmax ) = 20.4 versus 19.2 ng/ml; time to maximum concentration (Tmax ) = 4 versus 6 minutes; area under the curve (AUC): 307.9 versus 312.6, respectively]. Compared with other EC products, Juul had shorter Tmax [4 minutes, (IQR = 2.5–4.0) versus 6.3 minutes, (IQR = 4.7 – 8.1), P = 0.012] and higher Cmax (28.9 (SD = 15.6) versus 10.6 (SD = 5.5), P = 0.013) despite a lower number of puffs (12.5 (SD = 4.2) versus 17.0 (SD = 4.2), P = 0.084). Compared with other e‐cigarette products, it also provided faster reduction of urges to smoke and obtained more favourable subjective ratings. Conclusion: Juul's PK profile and user ratings suggest that it could be more effective than other EC products in helping smokers to quit smoking, but it may also have a higher potential to generate regular use in non‐smokers.